2020
DOI: 10.1002/pro.3845
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocytoplasmic transport of intrinsically disordered proteins studied by high‐speed super‐resolution microscopy

Abstract: Both natively folded and intrinsically disordered proteins (IDPs) destined for the nucleus need to transport through the nuclear pore complexes (NPCs) in eukaryotic cells. NPCs allow for passive diffusion of small folded proteins while barricading large ones, unless they are facilitated by nuclear transport receptors. However, whether nucleocytoplasmic transport of IDPs would follow these rules remains unknown. By using a high-speed super-resolution fluorescence microscopy, we have measured transport kinetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 58 publications
2
11
1
Order By: Relevance
“…Therefore, importins are capable of binding to both paralogues, NUPR1L and NUPR1, as we had already demonstrated the binding to the latter protein [ 23 ]. These findings are at variance with recent results obtained by fluorescence, where other IDPs were suggested to translocate into the nucleus without the need for the nucleus-cytoplasm transport machinery [ 39 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, importins are capable of binding to both paralogues, NUPR1L and NUPR1, as we had already demonstrated the binding to the latter protein [ 23 ]. These findings are at variance with recent results obtained by fluorescence, where other IDPs were suggested to translocate into the nucleus without the need for the nucleus-cytoplasm transport machinery [ 39 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The present results also suggested that not only the location (first two coding vs. last coding exons) and type (missense vs. truncation/frameshift) of SOX10 mutations, but also the altered levels of protein expression of the SOX10 missense variants and their molecular weight, including the aa composition (ratio of charged/hydrophobic aas) of the mutant proteins, may determine the severity of the expressed phenotype (Junod et al, 2020). These results also suggest that phenotypic severity may be regulated by the differential expression of each mutant protein, influenced by the activation versus escaping NMD pathway and other yet unknown factors.…”
Section: Discussionsupporting
confidence: 56%
“…However, a mutant protein was also produced, as shown by immunofluorescence study, but the protein was too small (3.1 kD) to be detected by western blot. Despite its lack of a NLS, the p.Ser30 ∗ variant was partly present in the nucleus, probably as a result of passive diffusion of the small (<63 kD) protein through the nuclear pore complex ( Gorlich and Mattaj, 1996 ; Junod et al, 2020 ). In summary, the molecular evidence supports a haploinsufficiency mechanism for this variant, resulting in classic WS4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, recently, we found that the nucleocytoplasmic transport of intrinsically disordered proteins (IDPs) was independent of molecular sizes and transport receptors that are well executed for folded proteins. Instead, the number of the charge and hydrophobic amino acid residues of the IDPs dominates their nuclear transport mechanisms [ 66 ]. In detail, the IDPs with a higher concentration of hydrophobic residues diffused through the NPCs with higher successful transport rates.…”
Section: Discussionmentioning
confidence: 99%